1984
DOI: 10.1002/1097-0142(19840801)54:3<387::aid-cncr2820540303>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter chemo-embolization effective for treating hepatocellular carcinoma. A histopathologic study

Abstract: A histopathologic study was done on livers from 14 patients who underwent surgery for hepatocellular carcinoma and who had been pretreated by a combination of intra‐arterial embolization of Gelfoam (Upjohn) plus intra‐arterial chemotherapy. This technique was effective as the excess vascularity of the tumor and the tumor bulk were reduced and resection was readily facilitated. For solitary tumors of less than 4 cm in diameter, this approach was particularly effective. As this combined treatment almost invariab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(68 citation statements)
references
References 12 publications
5
63
0
Order By: Relevance
“…Similarly, a previous histologic study evaluating the effect of chemoembolization showed that it is effective for encapsulated HCC measuring between 2.3 and 5.5 cm in diameter [25] . TAE is usually less effective for HCC smaller than 2 cm in diameter [27,29] .…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Similarly, a previous histologic study evaluating the effect of chemoembolization showed that it is effective for encapsulated HCC measuring between 2.3 and 5.5 cm in diameter [25] . TAE is usually less effective for HCC smaller than 2 cm in diameter [27,29] .…”
Section: Discussionmentioning
confidence: 75%
“…According to our results, previous pathological studies performed on liver resection following transarterial chemoembolization [22,23] demonstrated that encapsulated HCCs are more responsive to the transcatheter treatment than nonencapsulated tumors. Interestingly, a significant correlation between the thickness of the capsule and the effectiveness of tumor necrosis after chemoembolization has also been documented [24,25] . The reason for the relatively poor necrosis of tumors without capsule is not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of preoperative TACE in reducing local and metastatic recurrence and prolonging survival remains controversial [18]. Preoperative TACE results in better disease-free survival if complete tumor necrosis can be achieved, but actually increases the risk of recurrence if only partial necrosis is induced [19]. In addition, the size of HCC at the commencement of chemoembolization is an important prognostic factor in predicting the ultimate response and survival [20].…”
Section: Discussion and Review Of The Literaturementioning
confidence: 91%
“…However, many questions exist regarding the effects of Lipiodol accumulation on the magnetic resonance imaging MRI signal obtained from HCC after Lp-TACE. A number of studies have indicated that high signal intensity on T1-weighted images in HCC after Lp-TACE is caused by hemorrhagic necrosis [4][5][6] , while other studies concluded that…”
Section: Introductionmentioning
confidence: 99%